.4(7-3x)=9+(4x-1)

Simple and best practice solution for .4(7-3x)=9+(4x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .4(7-3x)=9+(4x-1) equation:


Simplifying
0.4(7 + -3x) = 9 + (4x + -1)
(7 * 0.4 + -3x * 0.4) = 9 + (4x + -1)
(2.8 + -1.2x) = 9 + (4x + -1)

Reorder the terms:
2.8 + -1.2x = 9 + (-1 + 4x)

Remove parenthesis around (-1 + 4x)
2.8 + -1.2x = 9 + -1 + 4x

Combine like terms: 9 + -1 = 8
2.8 + -1.2x = 8 + 4x

Solving
2.8 + -1.2x = 8 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
2.8 + -1.2x + -4x = 8 + 4x + -4x

Combine like terms: -1.2x + -4x = -5.2x
2.8 + -5.2x = 8 + 4x + -4x

Combine like terms: 4x + -4x = 0
2.8 + -5.2x = 8 + 0
2.8 + -5.2x = 8

Add '-2.8' to each side of the equation.
2.8 + -2.8 + -5.2x = 8 + -2.8

Combine like terms: 2.8 + -2.8 = 0.0
0.0 + -5.2x = 8 + -2.8
-5.2x = 8 + -2.8

Combine like terms: 8 + -2.8 = 5.2
-5.2x = 5.2

Divide each side by '-5.2'.
x = -1

Simplifying
x = -1

See similar equations:

| 5x+8x+11x= | | -40x+36x=30x-45 | | 2b^2+36-9=0 | | 4x-3=9x+9 | | 5x^3-3x^2-5x+3=5x^2-4x-1 | | y=[100+.75(y-150)]+100+100 | | 2v^2-3v+1=0 | | (x^2)+(11x)=0 | | y=-16+4x | | y=4x+-16 | | 2x+20=60+x | | 4(3x+7)=16 | | x^2-4x^2+3=0 | | (x^2)-(6x)=0 | | (4x^2+2x)(5x-4)= | | -1.5x+y=5 | | (x^2)-(6x)=o | | (5x-3)(x+1)(x-1)=0 | | 3x-6=5x+60 | | 5y+7=2y+11 | | -13+2x=-52+35x(fraction) | | 10a+b=8a+8b | | 43x+7=16 | | (5x-3)(x+1)(x-1)=(5x+1)(5x-1)x | | 7000=(1+0.0425t) | | 58-2x=8-7x | | 2(y-9)=3Y-8 | | 4(2x-3)-7x+5=11 | | 4x+2x+9+x+4=34 | | (2x+2)(3x^2-x+2)= | | -3(1)-3= | | y=[100+.75(y-100)]+100+100 |

Equations solver categories